A Power Estimation Method for Energy Efficient Wireless Sensor Network - Avina H. Dhangare (Journal of Power Electronics and Devices, 2019)
Wireless sensor networks (WSN) are composed of large number of sensor node with restricted energy. The energy is one of the most important terms in wireless sensor networks problem. Sensor node of WSN consists of processor unit, memory unit and power supply. Wireless sensor node is battery operated, therefore the biggest challenge in field of wireless sensor is the lifetimes of WSN node which can be improve by achieving communication with low power consumption. So in this proposed work, a path metric that accurately captures the expected number of link layer transmission required for reliable end to end packet delivery with minimum number of retransmission are considered; we analytically computed estimated cost with direct data transmission within the node and with shortest path between those nodes. Power is analyzed in terms of minimum cost which is the function of distance, number of packets used for transmission along with numbers of permissible hops. Comparative results are shown between time v/s delay, time v/s direct estimated cost and estimation with shortest minimum retransmission path, with variable data packets rate and number of hops. So, with the proper selection of data packet rate and number of hops for end to end transmission considerable reduction in power consumption can be obtained.